High-content high-strength phosphogypsum pavement base material and preparation method thereof
Patent Information
- Application Number
- CN202511198630.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本申请提供了一种高掺量高强度磷石膏路面基层材料及其制备方法,解决或部分解决了现有技术只能将磷石膏作为添加料或辅助材料在道路工程中进行应用,掺量太低无法实现废弃磷石膏规模化资源化利用的技术问题,实现磷石膏固废高效资源转化,在完全替代传统天然骨料制备路面基层材料的同时,兼具显著的经济性与生态效益,在推动固废资源综合利用领域具有重要工程应用价值和显著的经济价值
[0024] This application utilizes waste phosphogypsum as the main raw material, achieving high-volume and efficient utilization of waste phosphogypsum in road base materials. It achieves a breakthrough by increasing the phosphogypsum content to 65-80%, providing a novel solution for the large-scale and efficient utilization of phosphogypsum. This application innovatively introduces a composite emulsion synergistic reinforcement technology, achieving a breakthrough improvement in material performance through a dual-action mechanism. The emulsified asphalt emulsion forms a three-dimensional interpenetrating network structure in the inorganic matrix, effectively filling pores and improving material density. The polymer emulsion, through molecular chain bridging, inhibits crack initiation and propagation at the microscale, endowing the material with excellent crack resistance. This synergistic effect of the organic-inorganic hybrid system enables the material to possess both ultra-high compressive strength and excellent toughness, with mechanical properties significantly superior to traditional inorganic cementitious materials, fully meeting the stringent load-bearing requirements of base materials in special scenarios such as heavy-duty traffic and airport runways.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to a high-content, high-strength phosphogypsum pavement base material and its preparation method. Background Technology
[0002] Phosphogypsum is an industrial byproduct of the wet process for producing phosphoric acid in phosphate fertilizer plants. For every ton of phosphoric acid produced, 4.5 to 5.5 tons of phosphogypsum are generated as a byproduct. The main component of phosphogypsum is calcium sulfate dihydrate, accounting for approximately 70% to 90% of its total mass, and it also contains other insoluble salts and harmful impurities such as eutectic phosphorus. Although the utilization rate of phosphogypsum has been increasing year by year, a large amount of phosphogypsum is still stockpiled, which not only occupies a significant amount of land resources but also pollutes the environment, seriously hindering the sustainable development of the phosphate chemical industry. Therefore, accelerating the comprehensive utilization of phosphogypsum has become an urgent task.
[0003] Currently, research on the application of phosphogypsum in road engineering mainly focuses on its use as an additive or auxiliary material, with generally low dosages, while research on its use as a primary material is relatively limited. Crushed stone, as a natural mineral filler in road base materials, is a non-renewable resource. Therefore, applying phosphogypsum to road base materials as a substitute for natural aggregates has extremely important engineering value and social significance.
[0004] However, phosphogypsum is highly hydrophilic and easily softens when exposed to water. When used as a primary material for base layers, it often faces problems such as difficulty in forming strength and poor water stability, which seriously affects its application in engineering. Summary of the Invention
[0005] This application provides a high-dosage, high-strength phosphogypsum pavement base material and its preparation method, which solves or partially solves the technical problem that existing technologies can only use phosphogypsum as an additive or auxiliary material in road engineering, and the dosage is too low to achieve large-scale resource utilization of waste phosphogypsum. It realizes the efficient resource conversion of phosphogypsum solid waste, and while completely replacing traditional natural aggregates in the preparation of pavement base materials, it also has significant economic and ecological benefits. It has important engineering application value and significant economic value in promoting the comprehensive utilization of solid waste resources.
[0006] The high-dosage, high-strength phosphogypsum pavement base material provided in this application comprises the following components: phosphogypsum, multi-component cementitious materials, and composite emulsion. The phosphogypsum and the multi-component cementitious materials constitute a consolidation component, and the composite emulsion accounts for (1-5)% of the mass fraction of the consolidation component.
[0007] The consolidation components, by mass percentage, comprise: 65-80% phosphogypsum, 3-8% cement, 10-20% slag, 5-10% fly ash, and 5-10% lime.
[0008] The composite emulsion includes an emulsified asphalt emulsion and a polymer emulsion, wherein the mass ratio of the emulsified asphalt emulsion to the polymer emulsion is (7-9):(1-3).
[0009] Preferably, the emulsified asphalt is a cationic emulsified asphalt with a solid content of 30-50% and a pH value of 2.0-5.0.
[0010] Preferably, the polymer emulsion is a styrene-acrylic emulsion.
[0011] Preferably, the phosphogypsum is obtained by drying, cooling and pulverizing waste phosphogypsum produced in industry, and the surface free water is removed by drying.
[0012] The particle size distribution of the phosphogypsum is below 0.3 mm.
[0013] Preferably, the slag is S95 grade granulated blast furnace slag with a specific surface area > 400 m². 2 / kg.
[0014] Preferably, the cement is 42.5 ordinary Portland cement.
[0015] Preferably, the fly ash is secondary fly ash with a water requirement ratio ≤105% and a loss on ignition ≤8%.
[0016] Preferably, the lime is high-calcium slaked lime with a Ca(OH)2 content ≥70%.
[0017] Based on the same inventive concept, this application also provides a method for preparing a high-dosage, high-strength phosphogypsum pavement base material, comprising the following steps:
[0018] Waste phosphogypsum is dried, cooled, crushed, and sieved to obtain the phosphogypsum.
[0019] The composite emulsion and water are stirred and mixed evenly to obtain mixture A;
[0020] After the sieved phosphogypsum is mixed and stirred evenly with the multi-component cementitious material and allowed to stand, mixture B is obtained;
[0021] After mixing the mixture A and the mixture B evenly, the high-content, high-strength phosphogypsum pavement base material is obtained.
[0022] Preferably, the temperature in the drying process of the waste phosphogypsum is controlled at 60℃~80℃ and the time is controlled at 6h~12h.
[0023] One or more technical solutions provided in the embodiments of this application have at least the following technical effects or advantages:
[0024] This application utilizes waste phosphogypsum as the main raw material, achieving high-volume and efficient utilization of waste phosphogypsum in road base materials. It achieves a breakthrough by increasing the phosphogypsum content to 65-80%, providing a novel solution for the large-scale and efficient utilization of phosphogypsum. This application innovatively introduces a composite emulsion synergistic reinforcement technology, achieving a breakthrough improvement in material performance through a dual-action mechanism. The emulsified asphalt emulsion forms a three-dimensional interpenetrating network structure in the inorganic matrix, effectively filling pores and improving material density. The polymer emulsion, through molecular chain bridging, inhibits crack initiation and propagation at the microscale, endowing the material with excellent crack resistance. This synergistic effect of the organic-inorganic hybrid system enables the material to possess both ultra-high compressive strength and excellent toughness, with mechanical properties significantly superior to traditional inorganic cementitious materials, fully meeting the stringent load-bearing requirements of base materials in special scenarios such as heavy-duty traffic and airport runways.
[0025] Meanwhile, this application breaks through the limitations of traditional sand and gravel aggregates, innovatively adopting a coarse aggregate-free system. It combines all-powder components with multi-element solid waste cementitious materials to fully activate the pozzolanic effect, significantly improving the material's cementitious performance. Compared to traditional road base materials, this system eliminates interfacial transition zone defects caused by coarse aggregates, resulting in a more uniform and dense material structure. This technology not only optimizes the material's microstructure but also significantly reduces the consumption of natural sand and gravel resources by over 90%, lowering material costs by 30-40%. This breakthrough has groundbreaking significance for alleviating mineral resource pressure and promoting green and low-carbon development. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0027] Unless otherwise specified, the experimental methods used in the following examples are conventional methods in the art. Unless otherwise specified, the experimental materials used in the following examples are commercially available. The cement used was P.O42.5 grade ordinary Portland cement produced by a certain company; the slag was S95 granulated blast furnace slag powder produced by a certain company; the phosphogypsum was a light gray acidic powder, prone to caking, and weakly acidic; the emulsified asphalt was a cationic matrix emulsified asphalt with a solid content of 40%, a brown liquid, purchased from a certain company; and provided by a company in Hebei Province. In the following comparative examples and examples, the mechanical properties of the phosphogypsum pavement base material were tested according to the test methods of "Highway Geotechnical Test Procedures" (JTGE 400-2007) and "Highway Engineering Inorganic Material Binder Stabilized Material Test Procedures" (JTG 3441-2024); the basic physical properties of the phosphogypsum pavement base material were determined according to the Highway Method A Compaction Standard T 0804-1994.
[0028] Unconfined compressive strength test: Standard specimens with a diameter of 50mm and a diameter of 50mm were statically pressed according to the test procedure, with a compaction degree of >98%. They were then placed in a standard curing chamber (20℃±2, humidity ≥95%) and cured to the required age. On the last day of the curing period, the specimens were taken out and immersed in water at 20℃±2 for 24 hours. After removing them and wiping the surface moisture with a soft cloth, the unconfined compressive strength test was carried out at a loading rate of 1mm / min. Six parallel specimens were used, and their representative values were taken.
[0029] Water stability test: In this test, cylindrical specimens of Φ50×50mm were prepared according to the preparation method of cylindrical specimens in the "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering". Different environmental conditions were simulated through multi-stage curing-immersion coupling. Three sets of differentiated test conditions were designed: (1) 6d standard curing and 1d immersion curing; (2) 5d standard curing + 2d immersion curing; (3) 4d standard curing + 3d immersion curing. The water stability coefficient is the percentage ratio of the unconfined compressive strength of the specimen under coupling conditions to the strength of the specimen under pure standard curing for 7 days. After the test, the ratio of compressive strength before and after water saturation was used as the softening coefficient of the material to evaluate the water resistance of the material.
[0030] Indirect tensile strength test: Standard specimens with a diameter of 50mm and a diameter of 50mm were made by static pressing according to the test procedure, with a compaction degree of >98%. They were then placed in a standard curing chamber (20℃±2, humidity ≥95%) and cured to the required age. On the last day of the curing period, the specimens were taken out and soaked in water at 20℃±2 for 24 hours. After removing them and wiping the surface moisture with a soft cloth, the indirect tensile strength test was carried out at a loading rate of 1mm / min. Six parallel specimens were used, and their representative values were taken.
[0031] Comparative Example 1
[0032] A phosphogypsum pavement base material, its composition and test results are as follows:
[0033] According to the corresponding mixing ratio, weigh all the required raw materials in quantitative quantities. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 65%, cement 5%, slag 10%, fly ash 10%, lime 10%; water accounts for 20% of the total mass of the consolidation component.
[0034] Mix phosphogypsum and multi-component cementitious materials evenly and let stand to obtain mixture A; pour water and mixture A into a mixing pot and stir continuously for 120-180 seconds to obtain road base material.
[0035] Samples were prepared and cured according to the test procedure. After testing, the standard specimens obtained had an unconfined compressive strength of 5.8 MPa at 7 days, 8.2 MPa at 14 days, and 10.5 MPa at 28 days. The indirect tensile strength at 7 days was 0.52 MPa, at 14 days it was 0.74 MPa, and at 28 days it was 0.95 MPa. The softening coefficients were K1 0.73, K2 0.81, and K3 0.89, respectively.
[0036] Comparative Example 2
[0037] A phosphogypsum pavement base material, its composition and test results are as follows:
[0038] According to the corresponding mixing ratio, weigh all the required raw materials quantitatively. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 65%, cement 5%, slag 15%, fly ash 7.5%, lime 7.5%; water accounts for 20% of the total mass of the consolidation component.
[0039] The standard specimens tested showed an unconfined compressive strength of 6.2 MPa at 7 days, 8.7 MPa at 14 days, and 11.2 MPa at 28 days. The indirect tensile strength was 0.56 MPa at 7 days, 0.79 MPa at 14 days, and 1.01 MPa at 28 days. The softening coefficients were K1 0.74, K2 0.83, and K3 0.90, respectively.
[0040] Comparative Example 3
[0041] A phosphogypsum pavement base material, its composition and test results are as follows:
[0042] According to the corresponding mixing ratio, weigh all the required raw materials in quantitative quantities. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 65%, cement 5%, slag 20%, fly ash 5%, lime 5%; water accounts for 20% of the total mass of the consolidation component.
[0043] The standard specimens tested showed an unconfined compressive strength of 5.3 MPa at 7 days, 7.6 MPa at 14 days, and 9.8 MPa at 28 days. The indirect tensile strength was 0.48 MPa at 7 days, 0.69 MPa at 14 days, and 0.88 MPa at 28 days. The softening coefficients were K1 0.70, K2 0.79, and K3 0.88, respectively.
[0044] Comparative Example 4
[0045] A phosphogypsum pavement base material, its composition and test results are as follows:
[0046] According to the corresponding mixing ratio, weigh all the required raw materials quantitatively. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 70%, cement 5%, slag 10%, fly ash 7.5%, lime 7.5%; water accounts for 20% of the total mass of the consolidation component.
[0047] The standard specimens tested showed an unconfined compressive strength of 4.9 MPa at 7 days, 7.0 MPa at 14 days, and 9.0 MPa at 28 days. The indirect tensile strength was 0.43 MPa at 7 days, 0.61 MPa at 14 days, and 0.79 MPa at 28 days. The softening coefficients were K1 0.65, K2 0.76, and K3 0.86, respectively.
[0048] Comparative Example 5
[0049] A phosphogypsum pavement base material, its composition and test results are as follows:
[0050] According to the corresponding mixing ratio, weigh all the required raw materials quantitatively. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 70%, cement 5%, slag 15%, fly ash 5%, lime 5%; water accounts for 20% of the total mass of the consolidation component.
[0051] The standard specimens tested showed an unconfined compressive strength of 5.5 MPa at 7 days, 7.9 MPa at 14 days, and 10.1 MPa at 28 days. The indirect tensile strength was 0.49 MPa at 7 days, 0.70 MPa at 14 days, and 0.90 MPa at 28 days. The softening coefficients were K1 0.68, K2 0.78, and K3 0.87, respectively.
[0052] Comparative Example 6
[0053] A phosphogypsum pavement base material, its composition and test results are as follows:
[0054] According to the corresponding mixing ratio, weigh all the required raw materials in quantitative quantities. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 70%, cement 5%, slag 20%, fly ash 2.5%, lime 2.5%; water accounts for 20% of the total mass of the consolidation component.
[0055] The standard specimens tested showed an unconfined compressive strength of 3.8 MPa at 7 days, 5.6 MPa at 14 days, and 7.5 MPa at 28 days. The indirect tensile strength was 0.33 MPa at 7 days, 0.49 MPa at 14 days, and 0.65 MPa at 28 days. The softening coefficients were K1 0.59, K2 0.70, and K3 0.82, respectively.
[0056] Comparative Example 7
[0057] A phosphogypsum pavement base material, its composition and test results are as follows:
[0058] According to the corresponding mixing ratio, weigh all the required raw materials in quantitative quantities. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 75%, cement 5%, slag 10%, fly ash 5%, lime 5%; water accounts for 20% of the total mass of the consolidation component.
[0059] The standard specimens tested showed an unconfined compressive strength of 3.5 MPa at 7 days, 5.1 MPa at 14 days, and 6.8 MPa at 28 days. The indirect tensile strength was 0.30 MPa at 7 days, 0.44 MPa at 14 days, and 0.59 MPa at 28 days. The softening coefficients were K1 0.52, K2 0.65, and K3 0.79, respectively.
[0060] Comparative Example 8
[0061] A phosphogypsum pavement base material, its composition and test results are as follows:
[0062] According to the corresponding mixing ratio, weigh all the required raw materials in quantitative quantities. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 75%, cement 5%, slag 15%, fly ash 2.5%, lime 2.5%; water accounts for 20% of the total mass of the consolidation component.
[0063] The standard specimens tested showed an unconfined compressive strength of 2.9 MPa at 7 days, 4.3 MPa at 14 days, and 5.8 MPa at 28 days. The indirect tensile strength was 0.25 MPa at 7 days, 0.37 MPa at 14 days, and 0.50 MPa at 28 days. The softening coefficients were K1 0.46, K2 0.60, and K3 0.76, respectively.
[0064] Comparative Example 9
[0065] A phosphogypsum pavement base material, its composition and test results are as follows:
[0066] According to the corresponding mixing ratio, weigh all the required raw materials in quantitative quantities. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 75%, cement 5%, slag 20%, fly ash 0%, lime 0%; water accounts for 20% of the total mass of the consolidation component.
[0067] The standard specimens tested showed an unconfined compressive strength of 1.8 MPa at 7 days, 2.7 MPa at 14 days, and 3.9 MPa at 28 days. The indirect tensile strength was 0.15 MPa at 7 days, 0.23 MPa at 14 days, and 0.33 MPa at 28 days. The softening coefficients were K1 0.34, K2 0.49, and K3 0.68, respectively.
[0068] Comparative Example 10
[0069] A phosphogypsum pavement base material, its composition and test results are as follows:
[0070] According to the corresponding mixing ratio, weigh all the required raw materials in quantitative quantities. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 80%, cement 5%, slag 10%, fly ash 2.5%, lime 2.5%; water accounts for 20% of the total mass of the consolidation component.
[0071] The standard specimens tested showed an unconfined compressive strength of 2.2 MPa at 7 days, 3.3 MPa at 14 days, and 4.6 MPa at 28 days. The indirect tensile strength was 0.19 MPa at 7 days, 0.28 MPa at 14 days, and 0.40 MPa at 28 days. The softening coefficients were K1 0.40, K2 0.54, and K3 0.72, respectively.
[0072] Comparative Example 11
[0073] A phosphogypsum pavement base material, its composition and test results are as follows:
[0074] According to the corresponding mixing ratio, weigh all the required raw materials quantitatively. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 80%, cement 5%, slag 15%, fly ash 0%, lime 0%; water accounts for 20% of the total mass of the consolidation component.
[0075] The standard specimens tested showed an unconfined compressive strength of 1.2 MPa at 7 days, 1.9 MPa at 14 days, and 2.8 MPa at 28 days. The indirect tensile strength was 0.11 MPa at 7 days, 0.17 MPa at 14 days, and 0.25 MPa at 28 days. The softening coefficients were K1 0.31, K2 0.44, and K3 0.62, respectively.
[0076] Comparative Example 12
[0077] A phosphogypsum pavement base material, its composition and test results are as follows:
[0078] According to the corresponding mixing ratio, weigh all the required raw materials quantitatively. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 80%, cement 5%, slag 0%, fly ash 7.5%, lime 7.5%; water accounts for 20% of the total mass of the consolidation component.
[0079] The standard specimens tested showed an unconfined compressive strength of 3.6 MPa at 7 days, 5.2 MPa at 14 days, and 7.0 MPa at 28 days. The indirect tensile strength was 0.32 MPa at 7 days, 0.46 MPa at 14 days, and 0.62 MPa at 28 days. The softening coefficients were K1 0.55, K2 0.69, and K3 0.81, respectively.
[0080] Example 1
[0081] A high-dosage, high-strength, water-resistant, and crack-resistant phosphogypsum pavement base material is prepared in a manner similar to that of Comparative Example 1, except that a composite emulsion is added.
[0082] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 65%, cement 5%, slag 10%, fly ash 10%, lime 10%; water accounts for 20% of the total mass of the consolidation component.
[0083] Mix phosphogypsum and multi-component cementitious materials until uniform and let stand to obtain mixture A; mix composite emulsion (mass ratio of emulsified asphalt emulsion to styrene-acrylic emulsion is 7:1) with water until uniform and let stand to obtain mixture B, the mass percentage of composite emulsion and consolidation component is 1%; pour mixture A and mixture B into a mixing pot and stir continuously for 150s to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.
[0084] The standard specimens tested showed an unconfined compressive strength of 12.8 MPa at 7 days, 16.5 MPa at 14 days, and 19.2 MPa at 28 days. The indirect tensile strength was 1.15 MPa at 7 days, 1.48 MPa at 14 days, and 1.73 MPa at 28 days. The softening coefficients were K1 0.85, K2 0.90, and K3 0.94, respectively.
[0085] Example 2
[0086] A high-dosage, high-strength, water-resistant, and crack-resistant phosphogypsum pavement base material is prepared using a method that is largely the same as in Example 1.
[0087] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 65%, cement 5%, slag 15%, fly ash 7.5%, lime 7.5%; water accounts for 20% of the total mass of the consolidation component.
[0088] Mix phosphogypsum and multi-component cementitious materials until uniform and let stand to obtain mixture A; mix composite emulsion (mass ratio of emulsified asphalt emulsion to styrene-acrylic emulsion is 7:1) with water until uniform and let stand to obtain mixture B, the mass percentage of composite emulsion and consolidation component is 1%; pour mixture A and mixture B into a mixing pot and stir continuously for 150s to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.
[0089] The standard specimens tested showed an unconfined compressive strength of 13.5 MPa at 7 days, 17.2 MPa at 14 days, and 20.3 MPa at 28 days. The indirect tensile strength was 1.22 MPa at 7 days, 1.55 MPa at 14 days, and 1.80 MPa at 28 days. The softening coefficients were K1 0.86, K2 0.91, and K3 0.95, respectively.
[0090] Example 3
[0091] A high-dosage, high-strength, water-resistant, and crack-resistant phosphogypsum pavement base material is prepared using a method that is largely the same as in Example 1.
[0092] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 70%, cement 5%, slag 10%, fly ash 7.5%, lime 7.5%; water accounts for 20% of the total mass of the consolidation component.
[0093] Mix phosphogypsum and multi-component cementitious materials until uniform and let stand to obtain mixture A; mix composite emulsion (mass ratio of emulsified asphalt emulsion to styrene-acrylic emulsion is 7:1) with water until uniform and let stand to obtain mixture B, the mass percentage of composite emulsion and consolidation component is 3%; pour mixture A and mixture B into a mixing pot and stir continuously for 150s to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.
[0094] The standard specimens tested showed an unconfined compressive strength of 11.9 MPa at 7 days, 15.3 MPa at 14 days, and 18.1 MPa at 28 days. The indirect tensile strength was 1.02 MPa at 7 days, 1.31 MPa at 14 days, and 1.58 MPa at 28 days. The softening coefficients were K1 0.83, K2 0.89, and K3 0.93, respectively.
[0095] Example 4
[0096] A high-dosage, high-strength, water-resistant, and crack-resistant phosphogypsum pavement base material is prepared using a method that is largely the same as in Example 1.
[0097] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 70%, cement 5%, slag 15%, fly ash 5%, lime 5%; water accounts for 20% of the total mass of the consolidation component.
[0098] Mix phosphogypsum and multi-component cementitious materials until uniform and let stand to obtain mixture A; mix composite emulsion (mass ratio of emulsified asphalt emulsion to styrene-acrylic emulsion is 7:1) with water until uniform and let stand to obtain mixture B, the mass percentage of composite emulsion and consolidation component is 3%; pour mixture A and mixture B into a mixing pot and stir continuously for 150s to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.
[0099] The standard specimens tested showed an unconfined compressive strength of 13.1 MPa at 7 days, 16.8 MPa at 14 days, and 19.6 MPa at 28 days. The indirect tensile strength was 1.18 MPa at 7 days, 1.51 MPa at 14 days, and 1.76 MPa at 28 days. The softening coefficients were K1 0.86, K2 0.91, and K3 0.94, respectively.
[0100] Example 5
[0101] A high-dosage, high-strength, water-resistant, and crack-resistant phosphogypsum pavement base material is prepared using a method that is largely the same as in Example 1.
[0102] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 80%, cement 5%, slag 10%, fly ash 2.5%, lime 2.5%; water accounts for 20% of the total mass of the consolidation component.
[0103] Mix phosphogypsum and multi-component cementitious materials until uniform and let stand to obtain mixture A; mix composite emulsion (mass ratio of emulsified asphalt emulsion to styrene-acrylic emulsion is 7:1) with water until uniform and let stand to obtain mixture B, the mass percentage of composite emulsion and consolidation component is 5%; pour mixture A and mixture B into a mixing pot and stir continuously for 150s to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.
[0104] The standard specimens tested showed an unconfined compressive strength of 10.2 MPa at 7 days, 13.5 MPa at 14 days, and 16.3 MPa at 28 days. The indirect tensile strength was 0.88 MPa at 7 days, 1.16 MPa at 14 days, and 1.40 MPa at 28 days. The softening coefficients were K1 0.82, K2 0.88, and K3 0.92, respectively.
[0105] Example 6
[0106] A high-dosage, high-strength, water-resistant, and crack-resistant phosphogypsum pavement base material is prepared using a method that is largely the same as in Example 1.
[0107] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 80%, cement 5%, slag 15%, fly ash 0%, lime 0%; water accounts for 20% of the total mass of the consolidation component.
[0108] Mix phosphogypsum and multi-component cementitious materials until uniform and let stand to obtain mixture A; mix composite emulsion (mass ratio of emulsified asphalt emulsion to styrene-acrylic emulsion is 7:1) with water until uniform and let stand to obtain mixture B, the mass percentage of composite emulsion and consolidation component is 5%; pour mixture A and mixture B into a mixing pot and stir continuously for 150s to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.
[0109] The standard specimens tested showed an unconfined compressive strength of 8.8 MPa at 7 days, 11.9 MPa at 14 days, and 15.0 MPa at 28 days. The indirect tensile strength was 0.76 MPa at 7 days, 1.03 MPa at 14 days, and 1.29 MPa at 28 days. The softening coefficients were K1 0.80, K2 0.86, and K3 0.91, respectively.
[0110] Table 1 Mix proportions of phosphogypsum pavement base materials
[0111]
[0112] Table 2. Relationship between 7-day unconfined compressive strength and traffic capacity of different base materials containing phosphogypsum.
[0113]
[0114] As shown in Table 2, the 7-day unconfined compressive strength of Examples 1-6 is significantly higher than that of Comparative Examples 1-12, and all of them meet the 5.0-7.0 MPa standard for extremely heavy / special transportation. The analysis based on the mix proportions in Table 1 is as follows:
[0115] Taking Comparative Example 2 and Example 2 as examples, both have the same consolidation component ratio, the difference being that Example 2 adds 1% composite emulsion. In the composite emulsion, emulsified asphalt fills the matrix pores to form a three-dimensional network structure, and styrene-acrylic emulsion enhances interfacial adhesion through molecular chain bridging. The two work synergistically to improve density, resulting in a 117.7% increase in strength. In Comparative Examples 7-12, when the phosphogypsum content increases to 75%-80% and no emulsion is added, the 7-day strength drops to 1.2-3.8 MPa because the high-content phosphogypsum lacks cementitious material support, leading to a loose structure. However, in Examples 5-6, through the "organic-inorganic hybrid" effect of the emulsion, the strength still reaches 8.8-10.2 MPa, which is 3-7 times higher than the comparative examples with the same content. This proves that the composite emulsion can effectively overcome the strength loss of high phosphogypsum content and meet the needs of heavy-duty traffic.
[0116] Table 3 Unconfined compressive strength and 28-day unconfined compressive strength of different base materials containing phosphogypsum
[0117]
[0118] As shown in Table 3, the 28-day compressive strength of Examples 1-6 is significantly higher than that of Comparative Examples 1-12, and the strength increases steadily with age. The analysis based on the mix proportions in Table 1 is as follows:
[0119] Taking the 28-day unconfined compressive strength of Comparative Example 2 and Example 2 as examples, the addition of the emulsion promotes the formation of a waterproof membrane in the matrix by the emulsified asphalt, reducing the erosion of cementitious products by moisture. Simultaneously, the styrene-acrylic emulsion enhances the bonding at the microcrack interface, making the CSH gel network denser. In Comparative Examples 9-11, when the cement content was reduced to 5% or replaced with slag, the 28-day strength was only 2.8-3.9 MPa due to the lack of sufficient Ca(OH)2 to activate the slag activity. However, in Example 6 (through the synergistic effect of the emulsion and cementitious materials), the 28-day strength reached 15.0 MPa, an increase of 436% compared to Comparative Example 11, indicating that the composite emulsion can activate the cementitious reaction of the high-content phosphogypsum system and promote continuous strength development. Furthermore, the 14-day strength increase of the Example was higher than that of the Comparative Examples, confirming the promoting effect of the emulsion on early strength improvement.
[0120] Table 4 Softening coefficients of different base materials containing phosphogypsum
[0121] serial number <![CDATA[K1]]> <![CDATA[K2]]> <![CDATA[K3]]> Comparative Example 1 0.73 0.81 0.89 Comparative Example 2 0.74 0.83 0.90 Comparative Example 3 0.70 0.79 0.88 Comparative Example 4 0.65 0.76 0.86 Comparative Example 5 0.68 0.78 0.87 Comparative Example 6 0.59 0.70 0.82 Comparative Example 7 0.52 0.65 0.79 Comparative Example 8 0.46 0.60 0.76 Comparative Example 9 0.34 0.49 0.68 Comparative Example 10 0.40 0.54 0.72 Comparative Example 11 0.31 0.44 0.62 Comparative Example 12 0.55 0.69 0.81 Example 1 0.85 0.90 0.94 Example 2 0.86 0.91 0.95 Example 3 0.83 0.89 0.93 Example 4 0.86 0.91 0.94 Example 5 0.82 0.88 0.92 Example 6 0.80 0.86 0.91
[0122] As shown in Table 4, the softening coefficients of Examples 1-6 (0.80-0.95) are significantly higher than those of Comparative Examples 1-12 (0.31-0.90). The analysis based on the proportions in Table 1 is as follows:
[0123] Taking Comparative Example 1 and Example 1 as examples, the addition of emulsion allows the emulsified asphalt to form a hydrophobic film in the matrix pores, blocking water penetration. The styrene-acrylic emulsion fills microcracks, reducing water penetration channels. Together, they increase the softening coefficient by 5.6%. In Comparative Examples 7-11, when the phosphogypsum content increased from 75% to 80%, the softening coefficient decreased to 0.62 because high-content phosphogypsum is highly hydrophilic and easily softens upon contact with water. However, in Examples 5-6, by increasing the emulsion content, the film-forming effect of the emulsified asphalt offsets the hydrophilicity of phosphogypsum, resulting in a softening coefficient of 0.91-0.92, an increase of 48.4% compared to Comparative Example 11. Comparative Example 12 added lime to increase the alkalinity of the system, promoting the formation of CSH gel from slag / fly ash and improving density. However, Example 6 further blocked the contact between water and phosphogypsum through emulsion film formation, further increasing the softening coefficient by 12.3%, proving that the composite emulsion is a key factor in improving water resistance.
[0124] Table 5. Indirect tensile strength of different base materials containing phosphogypsum at 7d, 14d, and 28d.
[0125]
[0126] As shown in Table 5, the 28-day indirect tensile strength of Examples 1-6 is 78%-80% higher than that of Comparative Examples 1-12. The analysis based on the mix proportions in Table 1 is as follows:
[0127] Taking Comparative Example 2 and Example 2 as examples, the polymer chains of the styrene-acrylic emulsion in the composite emulsion form a "bridging effect" between microcracks. When the cracks propagate, the molecular chains consume fracture energy through tensile deformation, while the emulsified asphalt fills the matrix pores and enhances toughness. The synergistic effect of both significantly improves crack resistance. In Comparative Examples 7-11, when the phosphogypsum content increases to 75%-80%, the indirect tensile strength decreases to 0.25-0.59 MPa because the high phosphogypsum content leads to increased matrix brittleness. However, in Examples 5-6, through the "toughening modification" of the emulsion, the indirect tensile strength reaches 1.29-1.40 MPa, an increase of 416% compared to Comparative Example 11. Furthermore, the increase in indirect tensile strength at 14 days in the examples is higher than that in the comparative examples, indicating that the composite emulsion inhibits microcrack initiation through interfacial bonding in the early stages, achieving full-process optimization of crack resistance.
[0128] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-content, high-strength phosphogypsum pavement base material, characterized in that, It includes the following components: phosphogypsum, multi-component cementitious material and composite emulsion, wherein the phosphogypsum and the multi-component cementitious material constitute a solidification component, and the composite emulsion accounts for (1-5)% of the mass fraction of the solidification component; The consolidation components, by mass percentage, comprise: 65-80% phosphogypsum, 3-8% cement, 10-20% slag, 5-10% fly ash, and 5-10% lime. The composite emulsion includes an emulsified asphalt emulsion and a polymer emulsion, wherein the mass ratio of the emulsified asphalt emulsion to the polymer emulsion is (7-9):(1-3).
2. The high-content, high-strength phosphogypsum pavement base material as described in claim 1, characterized in that, The emulsified asphalt is a cationic emulsified asphalt with a solid content of 30-50% and a pH value of 2.0-5.
0.
3. The high-content, high-strength phosphogypsum pavement base material as described in claim 1, characterized in that, The polymer emulsion is a styrene-acrylic emulsion.
4. The high-content, high-strength phosphogypsum pavement base material as described in claim 1, characterized in that, The phosphogypsum is obtained by drying, cooling and pulverizing waste phosphogypsum produced in industry; The particle size distribution of the phosphogypsum is below 0.3 mm.
5. The high-content, high-strength phosphogypsum pavement base material as described in claim 1, characterized in that, The slag is S95 grade granulated blast furnace slag with a specific surface area > 400 m². 2 / kg.
6. The high-content, high-strength phosphogypsum pavement base material as described in claim 1, characterized in that, The cement is 42.5 ordinary Portland cement.
7. The high-content, high-strength phosphogypsum pavement base material as described in claim 1, characterized in that, The fly ash is grade II fly ash, with a water requirement ratio ≤105% and a loss on ignition ≤8%.
8. The high-content, high-strength phosphogypsum pavement base material as described in claim 1, characterized in that, The lime is high-calcium slaked lime with a Ca(OH)2 content ≥70%.
9. A method for preparing a high-content, high-strength phosphogypsum pavement base material, characterized in that, The preparation of the high-dosage, high-strength phosphogypsum pavement base material according to any one of claims 1 to 8 includes the following steps: Waste phosphogypsum is dried, cooled, crushed, and sieved to obtain the phosphogypsum. The composite emulsion and water are stirred and mixed evenly to obtain mixture A; After the sieved phosphogypsum is mixed and stirred evenly with the multi-component cementitious material and allowed to stand, mixture B is obtained; After mixing the mixture A and the mixture B evenly, the high-content, high-strength phosphogypsum pavement base material is obtained.
10. The method for preparing high-content, high-strength phosphogypsum pavement base material as described in claim 9, characterized in that, The temperature during the drying process of the waste phosphogypsum is controlled at 60℃~80℃, and the time is controlled at 6h~12h.